2022
DOI: 10.1111/cts.13376
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a pragmatic clinical trial to tailor opioids for acute pain on behalf of the IGNITE ADOPT PGx investigators

Abstract: Opioid prescribing for postoperative pain management is challenging because of inter‐patient variability in opioid response and concern about opioid addiction. Tramadol, hydrocodone, and codeine depend on the cytochrome P450 2D6 (CYP2D6) enzyme for formation of highly potent metabolites. Individuals with reduced or absent CYP2D6 activity (i.e., intermediate metabolizers [IMs] or poor metabolizers [PMs], respectively) have lower concentrations of potent opioid metabolites and potentially inadequate pain control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The design of the ADOPT‐PGx acute pain trial was described previously. 24 In the depression trial, participants were randomly assigned to two groups: one that receives recommendations for SSRI therapy guided by genotyping CYP2C19 and CYP2D6 (immediate genotyped arm), and the other that follows the conventional approach for SSRI prescription and dosing to manage depression symptoms, with genotyping delayed until after completing trial procedures. The study assessed patient‐reported outcomes at several time points: baseline, 1 month, 3 months, and 6 months.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The design of the ADOPT‐PGx acute pain trial was described previously. 24 In the depression trial, participants were randomly assigned to two groups: one that receives recommendations for SSRI therapy guided by genotyping CYP2C19 and CYP2D6 (immediate genotyped arm), and the other that follows the conventional approach for SSRI prescription and dosing to manage depression symptoms, with genotyping delayed until after completing trial procedures. The study assessed patient‐reported outcomes at several time points: baseline, 1 month, 3 months, and 6 months.…”
Section: Methodsmentioning
confidence: 99%
“… 27 This process has been described in detail elsewhere, and a parallel process for determining activity scores and assigning clinical CYP2D6 phenotype was utilized for this study. 16 , 24 Two commonly used antidepressants (fluoxetine and paroxetine) are also potent CYP2D6 inhibitors. For the trial, patients on one of these antidepressants which inhibit CYP2D6 were not considered to be phenoconverted to an intermediate or poor metabolizer phenotype, as it was assumed the CYP2D6‐inhibitor antidepressant would be stopped for the new therapy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thomas et al evaluated the management of postsurgical pain based on CYP2D6 phenotype [79]. Good results were also achieved by Cavallari et al: this trial encouraged the use of CYP2D6 genotyping in clinical practice, to be taken into account in conjunction with the use of CYP2D6 inhibitors, to guide customized opioid dosing to enhance postoperative pain control [78]. In the orofacial pain and Temporomandibular disorders (TMD), the use of PM needs great effort.…”
Section: Precision Medicine Approach To Pain and Temporomandibular Di...mentioning
confidence: 99%